Pattern-based Business Model Development for Cyber-Physical Production Systems - Rudtsch, Vinzent; Gausemeier, Jürgen; Gesing, Judith; Mittag, Tobias; Peter, Stefan

Virtual Reality based Conjoint Analysis for Early Customer Integration in Industrial Product Development - Backhaus, Klaus; Jasper, Jonas; Westhoff, Katharina; Gausemeier, Jürgen; Grafe, Michael; Stöcklein, Jörg

Conceptual Design of a Self-Optimising Production Control System - Mittag, Tobias; Gausemeier, Jürgen; Gräßler, Iris; Iwanek, Peter; Köchling, Daniel; Petersen, Marcus
Current production control systems cannot react appropriately to unknown situations (e.g. the dispatch of rush jobs). They are only able to react on known situations with a predefined behaviour. In this paper the paradigm of self-optimisation will be transferred to the production control level by using a procedure model to design a self-optimising production control system. The production control is then able to react autonomously on changing operational conditions and to deduce new reaction strategies for occurring faults or disturbances. A rule based decision model is the core of the conceptual design. It is based on known and possible future faults and deducts reaction strategies. Simultaneously to them, a simulation model will be proposed, that simulates and evaluates suitable strategies.

Pr {\ "a} ventive product protection - a holistic approach for ü r threat analysis - Eckelt, Daniel; Altemeier, Katharina; Kliewe, Daniel (Industry Management)

Using the scenario technique for diversification opportunities - systematic identification of search fields at SKF GmbH - G {\ "o} tz, Johannes; Schulz, Ingo; Wiederkehr, Olga (10th Symposium on Foresight and Technology Planning)

Systematics for the development of business models in product creation - K {\ "o} ster, Oliver

System for planning cross-industry innovations - Echterhoff, Niklas

A Design Framework for Developing a Reconfigurable Driving Simulator - Hassan, Bassem

Process for developing business model-oriented diversification strategies - Lehner, Markus

Introduction to Self-optimization - Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter (Design Methodology for Intelligent Technical Systems)

From Mechatronics to Intelligent Technical Systems - Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter; Vaßholz, Mareen (Design Methodology for Intelligent Technical Systems)

Specification Technique CONSENS for the Description of Self-Optimizing Systems - Dorociak, Rafal; Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter (Design Methodology for Intelligent Technical Systems)

Methodology for the Selection of Dependability Methods for the Development of Self-optimizing Systems - Dorociak, Rafal; Gausemeier, Jürgen; Iwanek, Peter (Dependability of Self-optimizing Mechatronic Systems)

Development of the Active Guidance Module - Dorociak, Rafal; Gausemeier, Jürgen; Iwanek, Peter; Meyer, Tobias; Sextro, Walter; Sondermann-Wölke, Christoph (Dependability of Self-optimizing Mechatronic Systems)

Design Methodology for Intelligent Technical Systems - Develop Intelligent Technical Systems of the Future

Dependability of Self-Optimizing Mechatronic Systems - Gausemeier, Jürgen; Rammig, Franz-Josef; Schäfer, Wilhelm; Sextro, Walter

Selecting Suitable Methods Using the Methodology - Dorociak, Rafal; Gausemeier, Jürgen; Iwanek, Peter; Meyer, Tobias; Sextro, Walter (Dependability of Self-optimizing Mechatronic Systems)

Selecting Suitable Methods Using the Methodology - Dorociak, Rafal; Gausemeier, Jürgen; Iwanek, Peter; Meyer, Tobias; Sextro, Walter (Dependability of Self-optimizing Mechatronic Systems)

Assessment of Production System Alternatives During Early Development Phase - Rudtsch, Vinzent; Gausemeier, Jürgen; Rehage, Gerald (Proceedings of the 12th Conference on Systens Engineering Research (CSER 14))

Development of Self-Optimizing Systems - Gausemeier, Jürgen; Vaßholz, Mareen (Dependability of Self-Optimizing Mechatronic Systems)

Development of Self-Optimizing Systems - Gausemeier, Jürgen; Korf, Sebastian; Porrmann, Mario; Stahl, Katharina; Sudmann, Oliver; Vaßholz, Mareen (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Driver-in-the-Loop-Simulation - Amelunxen, Hendrik; Berssenbrügge, Jan; Schmid, Christoph (Automobil Elektronik)

Methods for the Domain-Spanning Conceptual Design - Anacker, Harald; Brenner, Christian; Dorociak, Rafal; Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter; Sch{\, Wilhelm; Vaßholz, Mareen (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Methods for the Domain-Spanning Conceptual Design - Anacker, Harald; Brenner, Christian; Dorociak, Rafal; Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter; Schäfer, Wilhelm; Vaßholz, Mareen (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Geschäftsmodellmuster für disruptive Technologien - Amshoft, Benjamin; Dülme, Christian; Echterfeld, Julian; Gausemeier, Jürgen

The development order as the basis for a forward-looking and system-oriented product creation - Wiederkehr, Olga; Dumitrescu, Roman; Gausemeier, J {\ "u} rgen (Systems Engineering Day 2014)

Framework for modeling a plausible system structure of mechatronic systems - Kaiser, Lydia

Challenges - Iwanek, Peter; Meyer, Tobias; Priesterjahn, Claudia; Sextro, Walter; Vaßholz, Mareen (Dependability of Self-optimizing Mechatronic Systems)

Strategic planning of market services in the context of Industry 4.0 - Gausemeier, J {\ "u} rgen; Amshoff, Benjamin; D ü lme, Christian; Kage, Martin (Foresight and Technology Planning)

Household Savings and Productive Capital Formation in Rural Vietnam: Insurance vs. Social Network - Gries, Thomas; Dung, Ha Van (Modern Economy)

Untersuchung des Erreichbarkeitsproblems in ungerichteten Graphen bezüglich den Komplexitätsklassen L und SL - Biermeier, Felix

Evaluierung von Initialisierungsmethoden für Fuzzy-k-means Algorithmen - Sauer, Malte

Erwerb von Handlungskompetenz in Communities of Practice - Bloh, Thiemo

Zur Bedeutung Anderer bei der Entwicklung von Expertise – Eine Analyse berufsbiographischer Narrationen von Grundschullehrkräften - Bloh, Thiemo

Korrosionsuntersuchungen an experimentellen und technisch relevanten Magnesiumlegierungen - Hoyer, Kay-Peter

Rainbow connection number of graph power and graph products - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

Rainbow connection number and radius - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

The setting behavior of dispersion adhesives during bonding of Wood Plastic Composites (WPC) - Moritzer, Elmar; Hopp, Matthias (67th Annual Assembly of the International Institute of Welding (IIW))

The same but not the same - Challenges in comparing patient opinions - Geierhos, Michaela; Schulze, Sabine

What is research ethics observing? An interdisciplinary {\ "a} re discussion between computational linguistics and qualitative-constructivist social research} - Geierhos, Michaela; Siri, Jasmin (Proceedings Research Ethics in Qualitative and Quantitative Social Research)

Ans {\ "a} sets for ü r an online optimization of the lot sizes in the Series production - Dangelmaier, Wilhelm

Modeling of the PLC Behavior in Intralogistics with Non-Autonomous Hybrid Petri-Nets - Kopecki, Lukas; Lauck, Sebastian

Information Systems for Composite Materials: Requirements and Challenges - Dangelmaier, Wilhelm; Sommer-Dittrich, Thomas; Streichhan, Jenny; Monhof, Markus (Applied Mechanics and Materials)

Comparative study on disambiguating acronyms in the scientific papers using the open knowledge base - Jeong, Do-Heon; Gim, Jangwon; Jung, Hanmin; Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 9th Asia Pacific International Conference on Information Science and Technology)

An Evolutionary Approach on Multi-objective Scheduling for Evolving Manufacturing Systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 47th Annual Hawaii International Conference on System Sciences)
New paradigms for designing manufacturing systems, such as adaptive and service-oriented manufacturing systems or self-optimizing resources, introduce new degrees of freedom into manufacturing control. These paradigms lead to the research question how human decision makers can be enabled to exploit the high adaptability of the new manufacturing systems in accordance to the current requirements arising from quickly changing market requirements and demand for sustainable manufacturing. This contribution extends a scheduling model for self-optimizing and service-oriented manufacturing systems through the consideration of alternative resources and introduces a multi-objective scheduling concept based on evolutionary algorithms in combination with a new optimized type of crossover operator.

Acceleration of Materialflow Simulations Using Model Coarsening by Token Sampling and Online Error Estimation and Accumulation Controlling - Renken, Hendrik

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Penser le Lexique-Grammaire)

Development of the RailCab Vehicle - Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Ober-Blöbaum, Sina; Priesterjahn, Claudia; Rasche, Christoph; Schäfer, Wilhelm; Steenken, Dominik; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Bright integrated photon-pair source for practical passive decoy-state quantum key distribution - Krapick, S.; Stefszky, Michael; Jachura, M.; Brecht, Benjamin; Avenhaus, M.; Silberhorn, Christine (Physical Review A)

Absence of pressure sensitivity of apparent wall slip in pressure-driven flow of non-colloidal suspensions - Pieper, Sven; Kirchhoff, Nadine; Schmid, Hans-Joachim (Rheologica Acta)
We investigated an explanation for the length dependence of apparent wall slip in capillary and slit die experiments that had been implied in earlier studies. Firstly, we used a very long slit die fitted with six equidistant pressure transducers and an adjustable outlet. It was found that, all other parameters being equal, the impact of pressure on the flow behavior of suspensions was not different from the impact on the unfilled matrix fluid. Particle-related properties, such as apparent wall slip, were therefore not influenced by pressure as assumed by other authors. Secondly, we determined wall slip velocities by both the Mooney method and numerical simulation, based on an implementation of Phillips constitutive equation for particle migration. This led to a similar length dependence of wall slip as had been reported in an earlier work. We concluded that this was due to the transient nature of particle migration and its interrelationship with apparent wall slip, rather than an influence of pressure.

Ultrafine Dust Filtration Using Precoat Materials Considering the Influence of Filter Media - Schiller, Sascha; Schmid, Hans-Joachim (Chemical Engineering & Technology)
Ultrafine dust separation from different sources like industry, traffic, or private households has become increasingly important in the last decade. A compact baghouse filter system has been developed which is suitable for pellet heaters. For filtration, a precoat material is required to prevent clogging of the filter media by the ultrafine dust particles. In order to ensure the best performance of this filter system, different combinations of filter media and precoat materials, e.g., grade efficiencies and the cake area load for the various filter media, were investigated in a special test rig. With this highly efficient technology, extremely high separation efficiencies of > 99 % and ultrafine dust concentrations of > 1 mg cm−3 could be reached in a long-term stable process.

Simulation of Capillary Bridges between Nanoscale Particles - Dörmann, Michael; Schmid, Hans-Joachim (Langmuir)
Capillary forces are very important as they exceed in general other adhesion forces. But at the same time the exact calculation of these forces is very complex, so often assumptions and approximations are used. Previous research was done with regard to micrometer sized particles, but the behavior of nanoscale particles is different. Hence, the results for micrometer sized particles cannot be directly transferred when considering nanoscale particles. Therefore, a simulation method was developed to calculate numerically the shape of a rotationally symmetrical capillary bridge between two spherical particles or a particle and a plate. The capillary bridge in the gap between the particles is formed due to capillary condensation and is in thermodynamic equilibrium with the gas phase. Hence the Kelvin equation and the Young–Laplace equation can be used to calculate the profile of the capillary bridge, depending on the relative humidity of the surrounding air. The bridge profile consists of several elements that are determined consecutively and interpolated linearly. After the shape is determined, the volume and force, divided into capillary pressure force and surface tension force, can be calculated. The validation of this numerical model will be shown by comparison with several different analytical calculations for micrometer-sized particles. Furthermore, it is demonstrated that two often used approximations, (1) the toroidal approximation and (2) the use of an effective radius, cannot be used for nanoscale particles without remarkable mistake. It will be discussed how the capillary force and its components depend on different parameters, like particle size, relative humidity, contact angle, and distance, respectively. The rupture of a capillary bridge due to particle separation will also be presented.

Outsourcing von Lagerdienstleistungen als operatives Entscheidungsproblem - Betz, Stefan (Logistikorientiertes Produktionsmanagement)

Verfahren zur Entwicklung geschäftsmodellorientierter Diversifikationsstrategien - Lehner, Markus

Systematik für die integrative Konzipierung der Montage auf Basis der Prinziplösung mechatronischer Systeme - Brandis, Rinje

Systematik zur Entwicklung von Geschäftsmodellen in der Produktentstehung - Köster, Oliver

Rahmenwerk zur Modellierung einer plausiblen Systemstruktur mechatronischer Systeme - Kaiser, Lydia

Systematik zur Planung von CrossIndustry-Innovationen - Echterhoff, Niklas

A Design Framework for Developing a Reconfigurable Driving Simulator - Hassan, Bassem

Model Consistency Management for Systems Engineering - Rieke, Jan

Beating Irrationality: Does Delegating to IT Alleviate the Sunk Cost Effect? - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Management Science)

Systematik der virtuellen Inbetriebnahme von automatisierten Produktionssystemen - Brökelmann, Jan

Using Income Accounting as the Theoretical Basis for Measuring IT Productivity - Kundisch, Dennis; Mittal, Neeraj; Nault, Barrie (Information Systems Research)

Don't take away my Status! - Evidence from the Restructuring of a Virtual Reward System - Mutter, Tobias; Kundisch, Dennis (Computer Networks)

Business Models - An Information Systems Research Agenda - Veit, Daniel; Clemons, Eric; Benlian, Alexander; Buxmann, Peter; Hess, Thomas; Kundisch, Dennis; Leimeister, Jan-Marco; Loos, Peter; Spann, Martin (Business & Information Systems Engineering)

Geschäftsmodelle - Eine Forschungsagenda für die Wirtschaftsinformatik - Veit, D.; Clemons, E.; Buxmann, A.; Hess, T.; Kundisch, Dennis; Leimeister, J.-M.; Loos, P.; Spann, M. (Wirtschaftsinformatik)

Analyzing Cost and Risk Interaction Effects in IT Project Portfolios - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (BIT - Banking and Information Technology)

Structural Quantification of Entanglement - Shahandeh, F.; Sperling, Jan; Vogel, W. (Physical Review Letters)

Detection of nonlocal superpositions - Gutiérrez-Esparza, A. J.; Pimenta, W. M.; Marques, B.; Matoso, A. A.; Sperling, Jan; Vogel, W.; Pádua, S. (Physical Review A)

Witnessing the degree of nonclassicality of light - Mraz, M.; Sperling, Jan; Vogel, W.; Hage, B. (Physical Review A)

Unified quantification of nonclassicality and entanglement - Vogel, W.; Sperling, Jan (Physical Review A)

Quantum state engineering by click counting - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review A)

Bipartite bound entanglement in continuous variables through degaussification - Steinhoff, F. E. S.; de Oliveira, M. C.; Sperling, Jan; Vogel, W. (Physical Review A)

Operational Gaussian Schmidt-number witnesses - Shahandeh, F.; Sperling, Jan; Vogel, W. (Physical Review A)

Kollektive Orientierungsmuster als Teil individueller Handlungskompetenz: Eine komparative Analyse kooperierender Grundschullehrkräfte - Bloh, Thiemo (Perspektiven auf inklusive Bildung)

Resonance chains in open systems, generalized zeta functions and clustering of the length spectrum - Barkhofen, Sonja; Faure, F; Weich, T (Nonlinearity)

Formation and interaction of resonance chains in the open three-disk system - Weich, T; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)

Spectral properties of microwave graphs with local absorption - Allgaier, Markus; Gehler, Stefan; Barkhofen, Sonja; Stöckmann, H.-J.; Kuhl, Ulrich (Physical Review E)

Twenty years of learning with the World Wide Web - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix
n the summer of 1994, courses at universities were supported for the first time through the use of the World Wide Web. With the introduction of this new technology, high expectations quickly arose that the established forms of teaching and learning in schools and universities would be replaced and that the institutions themselves might even prove to be superfluous. Twenty years later, it turns out that there is a great gap between hope and reality. Some of the ideas at the time that, for example, having access to the world's knowledge at any time would make textbooks superfluous, turned out to be naive in retrospect. Characteristic of the ideas at that time was the assumption that didactic and organizational problems of teaching and learning could be solved purely technically.

Zwischen Design und Flexibilität - Zur Ergonomie des Flat Design - Winkelnkemper, Felix; Keil, Reinhard

Forschendes Lernen durch semantisches Positionieren - Jakoblew , Marcel; Keil, Reinhard; Winkelnkemper, Felix (Proceedings der HDI 2014)

Hypothesengeleitete Gestaltung von Benutzungsoberflächen - Keil, Reinhard; Schild, Christian

Knowledge integration processes and distributed knowledge organization - Keil, Reinhard

Erklärungsfaktoren für Einstellungen von Lehrerinnen und Lehrern zum inklusiven Unterricht in der Grundschule - Hellmich, Frank; Görel, Gamze (Zeitschrift für Bildungsforschung)

Einstellungen zur Inklusion und Vorerfahrungen aus dem „Gemeinsamen Unterricht“ bei Lehrkräften in der Grundschule - Hellmich, Frank; Görel, Gamze (Forschung zu inklusiver Bildung. Gemeinsam anders lehren und lernen)

Wahrnehmung von Rückmeldungen durch Kinder im Leseunterricht der Grundschule im Zusammenhang mit ihrem Leseverständnis und ihren selbstbezogenen Kognitionen und Motivationen. - Hellmich, Frank; Hoya, Fabian Karl (Empirische Bildungsforschung und evidenzbasierte Reformen im Bildungswesen)

Individuelles Feedback in heterogen zusammengesetzten Lerngruppen im Leseunterricht der Grundschule – Befunde aus einer empirischen Studie - Hoya, Fabian Karl; Hellmich, Frank (Perspektiven auf inklusive Bildung)

Die Rolle von Klassenklima und Rückmeldungen für Selbstkonzept, Motivation und Leseleistung bei Kindern im Grundschulunterricht – Ergebnisse aus einer empirischen Studie - Hellmich, Frank; Hoya, Fabian Karl (Beziehungen in Schule und Unterricht (Teil 2). Soziokulturelle und schulische Einflüsse auf pädagogische Beziehungen)

Die Rolle von Klassenklima und Rückmeldungen für Selbstkonzept, Motivation und Leseleistung bei Kindern im Grundschulunterricht – Ergebnisse aus einer empirischen Studie - Hellmich, Frank; Hoya, Fabian Karl (Schulpädagogik-heute)

Lesefähigkeiten und metakognitive Lesestrategien bei Kindern mit Deutsch als Erst- und Zweitsprache im Vergleich - Hellmich, Frank; Niebuhr-Siebert, Sandra; Förster, Sabrina (Individuelle Förderung und Lernen in der Gemeinschaft)

Kleinräumige lebenslagenbezogene kommunale Sozialberichterstattung für die Stadt Guben - Meier-Gräwe, Uta; Klünder, Nina; Pathenschneider, Mira

Prospective relevance of dietary patterns at the beginning and during the course of primary school to the development of body composition - Diethelm, Katharina; Günther, Anke L. B.; Schulze, Matthias B.; Standl, Marie; Heinrich, Joachim; Buyken, Anette (British Journal of Nutrition)
Primary school years seem to represent a critical period for the development of overweight and obesity. However, only a few studies have analysed the prospective relationship between dietary patterns and weight status in children. The aims of the present study were to identify dietary patterns at the beginning of and during the primary school period and to examine their relevance to the development of body composition. Nutritional and anthropometric data from 371 participants of the Dortmund Nutritional and Longitudinally Designed (DONALD) Study at the beginning (ages 6 and 7 years) and end (ages 10 and 11 years) of the primary school period were used. Principal component analyses (PCA) were conducted to identify dietary patterns, which were regressed on changes in BMI and fat mass index (FMI) between ages 6 and 7 years and ages 10 and 11 years. Reduced rank regression (RRR) was used to directly extract patterns explaining variation in changes in BMI and FMI between ages 6 and 7 years and ages 10 and 11 years. PCA yielded interpretable patterns of dietary changes at the beginning of and during the primary school period, which were not related to changes in body composition. Conversely, RRR allowed identifying predictive patterns: higher baseline intakes of white bread and lower baseline intakes of whole-grain products as well as increases in the consumption of savoury snacks, sausages and cheese during primary school years independently predicted increases in BMI and FMI during the primary school period. In conclusion, selection of unfavourable carbohydrate sources at the beginning of the primary school period and increases in the consumption of processed savoury foods during primary school years may adversely affect the development of body composition during the course of primary school.

Dietary glycemic load, insulin load, and weight loss in obese, insulin resistant adolescents: RESIST study - Joslowski, Gesa; Halim, Jocelyn; Goletzke, Janina; Gow, Megan; Ho, Mandy; Louie, Jimmy C.-Y.; Buyken, Anette; Cowell, Chris T.; Garnett, Sarah P. (Clinical Nutrition)

Association between carbohydrate quality and inflammatory markers: systematic review of observational and interventional studies - Buyken, Anette; Goletzke, Janina; Joslowski, Gesa; Felbick, Anna; Cheng, Guo; Herder, Christian; Brand-Miller, Jennie C (The American Journal of Clinical Nutrition)

Velocities of weight, height and fat mass gain during potentially critical periods of growth are decisive for adult body composition - Cheng, G; Bolzenius, K; Joslowski, G; Günther, A L B; Kroke, A; Heinrich, J; Buyken, Anette (European Journal of Clinical Nutrition)

Increased Intake of Carbohydrates from Sources with a Higher Glycemic Index and Lower Consumption of Whole Grains during Puberty Are Prospectively Associated with Higher IL-6 Concentrations in Younger Adulthood among Healthy Individuals - Goletzke, Janina; Buyken, Anette; Joslowski, Gesa; Bolzenius, Katja; Remer, Thomas; Carstensen, Maren; Egert, Sarah; Nöthlings, Ute; Rathmann, Wolfgang; Roden, Michael; Herder, Christian (The Journal of Nutrition)

Low Carbon Economics - Theory and application - Gries, Thomas (Low Carbon Economics)

MaxiNet: Distributed Emulation of Software-Defined Networks - Wette, Philip; Dräxler, Martin; Schwabe, Arne; Wallaschek, Felix; Zahraee, Mohammad Hassan; Karl, Holger (Proceedings of the 2014 IFIP Networking Conference (Networking 2014))
Network emulations are widely used for testing novel network protocols and routing algorithms in realistic scenarios. Up to now, there is no emulation tool that is able to emulate large software-deﬁned data center networks that consist of several thousand nodes. Mininet is the most common tool to emulate Software-Deﬁned Networks of several hundred nodes. We extend Mininet to span an emulated network over several physical machines, making it possible to emulate networks of several thousand nodes on just a handful of physical machines. This enables us to emulate, e.g., large data center networks. To test this approach, we additionally introduce a trafﬁc generator for data center trafﬁc. Since there are no data center trafﬁc traces publicly available we use the results of two recent trafﬁc studies to create synthetic trafﬁc. We show the design and discuss some challenges we had in building our trafﬁc generator. As a showcase for our work we emulated a data center consisting of 3200 hosts on a cluster of only 12 physical machines. We show the resulting workloads and the trade-offs involved.

Zur Ausbreitung und Behinderung von Epidemien - Eine Netzwerkanalyse - Drigalsky, Liesa

Webcam application using virtual FPGA - Wu, Sen